2009
DOI: 10.1258/la.2008.008066
|View full text |Cite
|
Sign up to set email alerts
|

The diet board: welfare impacts of a novel method of dietary restriction in laboratory rats

Abstract: Laboratory rats are commonly fed ad libitum (AL). Moderate dietary restriction (DR) decreases mortality and morbidity when compared with AL feeding, but there are several obstacles to the implementation of DR. Traditional methods of restricted feeding disrupt normal diurnal eating rhythms and are not compatible with group housing. We have designed a novel method, the diet board, to restrict the feeding of group-housed rats. Animals fed from the diet board had 15% lower body weight than the AL-fed animals at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…Furthermore, adrenal glands were larger in ad-libitum fed controls than rats restricted to 85%BW [24]. These results suggest that food restriction up to 25% loss of body weight does not adversely affect animal welfare [22]. Furthermore, the resulting higher motivation significantly reduces duration of experimental procedures.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, adrenal glands were larger in ad-libitum fed controls than rats restricted to 85%BW [24]. These results suggest that food restriction up to 25% loss of body weight does not adversely affect animal welfare [22]. Furthermore, the resulting higher motivation significantly reduces duration of experimental procedures.…”
Section: Discussionmentioning
confidence: 74%
“…Although compared to ad-libitum fed controls rats restricted to 85%BW had higher corticosterone levels overall, the difference was not significant between groups at any of the 5 weekly measures [21]. Another study found no difference in corticosterone levels between food restricted and ad libitum-fed rats [22]. When exposed to restraint stress, calorie restricted rats had significantly lower corticosterone levels than ad libitum-fed rats, suggesting lowered stress reactivity with calorie restriction [23].…”
Section: Discussionmentioning
confidence: 88%
“…It is secreted in a diurnal rhythm; in rats, plasma corticosterone levels peak in the early dark phase and reach a nadir in the early light phase. We collected plasma corticosterone in the early light phase to allow small differences between groups to be detected (33). Rats housed with both tubing and chew sticks had the lowest plasma corticosterone, which suggests that environmental enrichment (particularly tubing) may reduce stress.…”
Section: Discussionmentioning
confidence: 99%
“…24 Using the diet board method, a higher corticosterone response was recorded but without observing any pathology associated with this reaction. 25 However, a majority of behavioural studies in diet restriction has only included individualized animals.…”
mentioning
confidence: 99%